Influencia de las temperaturas de primavera en la producción de cerdos ibéricos de montanera en la provincia de Badajoz ( Extremadura , España ). - Gonzalo, J; Poblaciones, M J; Olea, L (Actas de la XLVIII RC de la SEEP. Huesca La multifuncionalidad de los pastos: producción ganadera sostenible y gestión de los ecosistemas, 2009)
The dehesa ecosystem in Iberian Peninsule south-western, has its most important management activity, from an economic, ecological and unrepeatable point of view, in the holm oak and cork oak fruits (acorn) use in an extensive way. The use of these fruits, together with herbaceous bio-mass, is mainly done by Iberian pigs in montanera from November to Febru- ary. In this work production levels (Iberian pigs in montanera/year) has been studied during 4 years (2003/04 to 2006/07). It has been also studied the production per “official” dehesa area (declared by Junta de Extremadura) and the production per cover by tree area, in Iberian pig montanera production areas in Badajoz (Extremadura), as well as the influence of the tem- peratures in flowering and productive periods in holm oak and cork oak. There is a significant production increase when minimum temperatures in February, March and April raise; likewise this production falls with a rise of the maxim temperatures in spring
Keywords: extensive pastures; Q. ilex ssp. ballota; Quercus suber; silvopastoral